A Case Report of Acute Esotropia in a Young Woman following Heroin Withdrawal - Bethel Shiferaw; Ebisa Bekele; Sara Syed; Lu Fan; Nirav Patel; Samia Qazi; Nicolas Biro (Case Reports in Medicine)
Introduction. Esotropia is a form of strabismus that can give the affected individual a “cross-eyed” appearance. Acute onset of esotropia is an uncommon form; in the vast majority of cases, no underlying neurological etiology is found. Case Presentation. A 22-year-old female with a long history of opiate abuse presented with acute onset of diplopia. She noted her eyes were crossing and started seeing double. She stopped using heroin 11 days prior to presentation. There was large inward deviation of her left eye. Convergence was difficult and accompanied by horizontal nystagmus. Diplopia resolved by covering each eye. Further investigations including imaging studies were normal. Discussion. Acute onset esotropia is rare and must be investigated right away to exclude central nervous system pathologies, where no opiates use is reported. Diplopia in the form of acute esotropia may manifest in up to 30% of individuals undergoing heroin withdrawal. Evaluating acute esotropia requires detailed information of medical history with an emphasis on drug use. Conclusion. Acute onset esotropia with double vision can be caused by abrupt withdrawal of opiates. This case should serve to raise awareness among health care professionals, to avoid costly and unnecessary diagnostic evaluations and interventions.